The Impact of Store Atmosphere, Service Quality, and Social Media Marketing on Purchase Decisions: Insight from the Coffee Shop Market (Case Study at Kedai Kopi Distrik Metropolitan Surabaya) - Kamila, Ikfina Rosyada; Pudjoprastyono, Hery; Azhar, Ratih Mukti (PT Inovasi Pratama Internasional, 2024)
This research aims to identify the influence of store atmosphere, service quality, and social media marketing on purchasing decisions at the Surabaya Metropolitan District Coffee Shop. Using quantitative methods with non-probability sampling techniques through purposive sampling, this research involved 115 respondents aged over 17 years who had bought and visited shops and had social media. Data was collected via Google Form and analyzed using Partial Least Square (PLS). The research results show that store atmosphere, service quality, and social media marketing have a positive influence on purchasing decisions. Consumers consider the design at Kedai Distrik Metropolitan to be quite unique by combining Vintage Chinatown-Sumatra themes. With a unique place and cheap product prices, consumers are happy to visit Kedai Kopi Distrik Metropolitan Surabaya, especially among teenagers.